Effects of Hypnotherapy on Pain Scale, Interleukin-6 Levels, and Quality of Life in Lung Cancer Patients Who Experience Cancer Pain - Widyasanti, Diana; Sutanto, Yusup Subagio; Septiawan, Debree; Aphridasari, Jatu; Reviono, Reviono (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: Pain is a common symptom in lung cancer patients and can affect their quality of life. Interleukin 6 (IL-6) plays a role in malignant cell proliferation and differentiation as well as the initiation and persistence of cancer pain. Hypnosis can reduce pain by reducing anxiety through relaxation and/or directly affecting neurophysiological activity that underlies the subjective experience of pain. This study aimed to evaluate hypnotherapy as a non-pharmacological method for managing cancer pain. Methods: Clinical trial of 30 subjects with quasi-experimental pre-test and post-test in treatment and control groups of lung cancer patients of NSCLC and SCLC stage III and IV who experienced cancer pain with pain scale ≥3 at RSUD Dr. Moewardi Surakarta in June to August 2023 with a consecutive sampling method. The treatment group received hypnotherapy intervention for 4 weeks. Subjects were assessed for pain scale, interleukin-6 levels, and FACT-L quality of life questionnaire. Results: A 4-week hypnotherapy intervention can significantly reduce the pain scale (P=0.0001) and improve the quality-of-life FACT-L (P=0.002) in lung cancer patients experiencing cancer pain. Hypnotherapy also significantly reduced IL-6 in the treatment group (P=0.008), but when compared with the control, the results were not significant (P=0.345). Conclusion: Hypnotherapy may reduce the pain scale and improve the quality of life of lung cancer patients who experience cancer pain, but does not significantly lower IL-6 levels.